Causative Organisms of Hospital Acquired Infections Among The Pediatric Patients In Tertiary Level Hospitals of Dhaka City - Miah, Khorshed Ali; Chowdhury, Md Zaforullah; Johora, Fatima Tuj; Khatun, Sumaiya (Update Dental College Journal, 2019)
Hospital acquired infections (HAI) are important causes of morbidity and mortality. The purpose of this study was to see the type of HAI and causative organisms of these infections among the paediatric patients in tertiary level hospitals of Dhaka city. This cross sectional study was conducted in three tertiary level hospitals in Dhaka City over a period of two years. A total of 1055 patients were observed and the study population comprised of all the admitted paediatric patients irrespective of sex and basic diseases who were found present during data collection period as admitted patients in the paediatric wards of the hospitals under study. Among 1055 pediatric patients admitted in all the three hospitals under study a total of 115 (10.9%) were affected by hospital acquired infections. Higher prevalence (14.0%) of Hospital-Acquired Infections (HAI) was found in surgery ward and the lower prevalence (9.2%) of HAI was found in medicine ward. The most common type of HAI was surgical wound infection 26(22.6%). Out of 115 HAI patients highest number 44(38.3%) were affected by staphylococcus aureusfollowed by E. coli23(20%). Update Dent. Coll. j: 2019; 9 (1): 23-28